Ecobrick as a smart solution for utilizing plastic and cloth waste in Jakarta - Yusuf, Yusnidar; Sukmawati, Wati; Riyanti, Hurip Budi (Journal of Community Service and Empowerment, 2020)
The problem of waste or garbage in large cities is also the focus of the Sustainable Development Goals (SDGs). This article aims to describe ecobrick activities as a solution to dealing with plastic and fabric waste in East Jakarta. The method used is empowerment by using several stages, namely the preparation stage and the implementation stage. Partners in this activity are women from RW 04 Perumnas Klender, East Jakarta, DKI Jakarta. Community service activities were carried out in March-April 2020. This service encourages partners to be actively involved, in the form of collecting various types of waste that have been determined, discussing materials, ecobrick techniques, and product manufacturing. To evaluate the activity, documentation is carried out in the form of attendance, photos, videos, and the resulting products. The service activities run according to plan, in the form of two stages, namely the preparation stage and the implementation stage (Socialization and explanation of plastic bottle and cloth waste, the impact on the environment and training in managing plastic bottle waste and leftover cloth into useful products). Partners are enthusiastic about participating in this â€œEcobrickâ€ activity and producing useful seat products. Partners can take their time to make this product. In addition to protecting the environment, this program also has added value for the community. The recommendation for the next program activity is training on marketing its products both conventionally and online, to deal with this pandemic condition.